Effect of dispersant on disperse dyeing for polyester fabric in silicone waterless dyeing system. Issue 2 (1st February 2022) - Pei, Liujun; Huang, Yawei; Zhang, Hongjuan; Wang, Jiping
Abstract: Disperse dye has a good dyeing property in silicone waterless dyeing system. However, the application of dispersants in this dyeing system has some problems such as unlevel dyeing, dull color, color spot. In this investigation, the effect of dispersant on the disperse dyeing was studied by adding sodium salt of poly naphthalene sulphonic acid into silicone waterless dyeing system. If the dispersant and the dyeing accelerant were used in the same bath, the fixation and level dyeing property of disperse dye would be influenced. Moreover, the more the amount of dispersant, the more dye aggregates on the fabric surface. The particle size and scanning electron microscope analysis were used to further investigate the aggregation of dyes. The results showed that more disperse dyes would be dispersed in the accelerant phase, and the aggregation of disperse dyes was enhanced, thus the aggregations of dyes and dispersants would be sticked on the fabric surface, which was the main reason leading to the poor level dyeing property. Therefore, the dispersant cannot be employed in the silicone waterless dyeing system with accelerant, which indicates the commercial disperse dye is not suitable for dyeing polyester fabric in the silicone waterless dyeing system.